Between Quilts, Books and Blogs—Auto/biography as Mediation (KULT_online, 2011)
Auto/Biography and Mediation, the proceedings of the fifth conference of the International Autobiography Association (IABA), edited by the American studies scholar Alfred Hornung, gathers a selection of almost 200 papers presented in Mainz in July 2006. The collection starts with Craig Howes’ reflections on working and living as an autobiography researcher, includes photography, dance and the internet as media of auto/biographic story telling, and concludes with the historical biographic functions of Chinese tombstones. These essays represent a wide interdisciplinary and thematic range, and survey mediation processes currently being examined in contemporary autobiography studies.